Asociación entre apego y riesgo suicida en adolescentes escolarizados de Colombia (2019)
Attachment is considered an important element in mental health, however, the relationship between attachment dimensions and suicidal risk has been little studied. Objective: To establish the association between trust, communication, and alienation and suicide risk in Colombian school adolescents. Subjects and Method: A cross-sectional observational study with an analytical component was designed in a randomized sample of 399 school adolescents (n = 1,901), according to a 30% prevalence of high suicide risk, members of the official educational institutions of Santa Marta (Colombia), the commune with the highest index of unsatisfied basic needs. Participants completed the Armsden and Greenberg attachment inventory and the Plutchik suicide risk scale, both validated locally. Reliability and association tests were calculated. Results: Adolescents were 339 adolescents between 13 and 19 years of age (M = 15.7, SD = 1.1), 57.8% were women. 59.9% of adolescents showed low trust in the mother, 57.2% low communication with the mother, 54.9% low alienation with the mother, 46.3%, low trust in the father, 49% low communication with the father, 48.7% low alienation with the father, and 28.6% high suicide risk. There was an association (adjusted) between high suicide risk and trust in the mother (OR = 2.00, 95%CI 1.12-3.57), communication with the mother (OR = 3.80, 95%CI 2.13-6.75), trust in the father (OR = 2.39, 95%CI 1.41-4.03), and communication with the father (OR = 2.01, 95%CI 1.19-3.37). Conclusions: Low trust and low communication with mother and father are risk factors for high suicide risk in Colombian school adolescents. Further research on this association in other populations is needed, as well as to consider other mediating factors. © 2019 Revista Chilena de Pediatria. All rights reserved.